Respon Daya Hambat Ekstrak Lantana camara Linn (Verbenaceae) Terhadap Fungi Trichophyton concentricum L. - Albina Tikupasang; Daniel Lantang (Jurusan Biologi FMIPA Universitas Cenderawasih, 2014)
Trichophyton concentricum is one of the fungi that causes dermatophytosis called Tinea imbricate which commonly occur in Papua. Indigenous people use Lantana camara to treat this mycosis. This study was conducted to investigate the antifungal activity of L. camara extract against T. concentricum. Completely Randomized Design with 5 treatment (25%, 50%, 75%, 100% concentration of L. camara extract and the reference antibiotic fluconazol as a positif control) and 4 replicates was used in this experiment. T. concentricum was isolated from patients suspected Tinea imbricate. Disc blank was soaked in L. camara extract and placed in the culture of T. concentricum, and then the inhibition zone was measured 24 hour after incubation. The result showed that L. camara extract was range between 6.7-8.6 mm and has low inhibition zone compared to the positive control (26.31mm). Key words: Antifungal, Lantana camara, Tricophyton concentricum, dermatophytosis.